2017
DOI: 10.1371/journal.pone.0175227
|View full text |Cite
|
Sign up to set email alerts
|

Prelinguistic human infants and great apes show different communicative strategies in a triadic request situation

Abstract: In the present research, we investigate the communicative strategies of 20 month old human infants and great apes when requesting rewards from a human experimenter. Infants and apes both adapted their signals to the attentional state of the experimenter as well as to the location of the reward. Yet, while infants frequently positioned themselves in front of the experimenter and pointed towards a distant reward, apes either remained in the experimenter’s line of sight and pointed towards him or moved out of sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…For example, one can either look at the experimenter and point to the reward, or gesture to the experimenter while looking at the reward, either way the referential triangle of joint attention is established. Yet a recent study, despite finding that chimpanzees pointed significantly more than humans, concluded that pointing was a triadic communication only in humans because humans directed the point to the experimenter, whereas the apes directed the point to the reward (Gretscher et al, 2017). This conclusion of a species‐difference in joint attention is based on using a shifting definition of pointing.…”
Section: The Process Of Decolonizing Joint Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one can either look at the experimenter and point to the reward, or gesture to the experimenter while looking at the reward, either way the referential triangle of joint attention is established. Yet a recent study, despite finding that chimpanzees pointed significantly more than humans, concluded that pointing was a triadic communication only in humans because humans directed the point to the experimenter, whereas the apes directed the point to the reward (Gretscher et al, 2017). This conclusion of a species‐difference in joint attention is based on using a shifting definition of pointing.…”
Section: The Process Of Decolonizing Joint Attentionmentioning
confidence: 99%
“…A related issue is whether results about social cognition based on a single group can generalize to the social cognition of the entire species. We know that there is diversity in the early JA‐related experiences in humans (Section II.III) and that there is diversity in the early JA‐related experiences in chimpanzees (Section II.V), but most comparative studies of social cognition disregard the influence of socio‐emotional experiences on social cognition outcomes (e.g., Dean et al, 2012; Gretscher et al, 2017; Herrmann et al, 2007; Povinelli & Eddy, 1993; Tomasello, 2019; Wobber et al, 2014). We cannot generalize from one sample with a particular type of early experience to the entire species if early experiences influence outcomes, as we know they do in chimpanzees (e.g., Bard, Dunbar, et al, 2014).…”
Section: The Process Of Decolonizing Joint Attentionmentioning
confidence: 99%
“…A reasonable interpretation is that this behaviour represents a kind of ritualized reaching to direct the attention of a human to a desired object. Evidence for this ritualized reaching interpretation is the study by van der Goot et al ( [17]; see also [18]), who presented chimpanzees with a desirable object next to a human but some distance away. The chimpanzees basically never pointed to the desired object, but instead locomoted over to it and then reached ritualistically through the mesh for it, whereas human infants tested in the same paradigm pointed from a distance using their index finger.…”
Section: (B) Referential Communicationmentioning
confidence: 99%
“…Since this "failed reach" is rewarded with a desired object (usually a food item) by a human, great apes may associatively learn, how (by reaching through the mesh) and when (in the presence of a human) to perform such a manual behavior. This non-communicative account is supported by results of Liszkowski and colleagues 32 who found that apes do not point for absent entities (presumably because there are no visual cues to induce this action), and by studies showing that apes try to get as close to the target object as possible before pointing 33,34 .…”
mentioning
confidence: 79%